Procedures for a recourse action in commercial paper according to the Mauritanian Commercial Code (مجلة أبحاث قانونية, 2024)
This research  has a subject  to study and analyze the requirements contained in Law No. 2000/05 issued on January 18, 2000 and the amendment included in the Mauritanian Commercial Code, these requirements related to the procedures for the exchange reversal suit for the bearer of a check against the guarantor of the fulfillment of the drawee, endorser and obligor, and the descriptive and analytical methods have been adopted for this The requirements and rulings with the opinions of the jurists in this regard.
Keywords: the check; the return of the currency; non-payment; the claim; procedures